Efficacy and safety of selinexor-based regimens as first-line treatments for elderly patients with diffuse large B-cell lymphoma: a real-world study - Jing Li; Jingjing Ge; Tingting Chen; Jianghua Cao; Xiaohua He; Shulan Wang; Hang Yang; Yu Wang; Peng Sun; Jiajia Huang; Shan Liu; Zhiming Li (BMC Cancer)
Abstract Purpose This study aimed to evaluate the efficacy and safety of selinexor-based regimens as first-line treatments for elderly patients with diffuse large B-cell lymphoma (DLBCL). Methods A retrospective analysis of 16 elderly patients with DLBCL who received selinexor-based regimens as first-line treatments at Sun Yat-sen University Cancer Center from November 2021 to September 2023 was conducted. The primary endpoint was the objective response rate (ORR), while the secondary endpoints included progression-free survival (PFS), duration of response (DOR), and safety. Results Among the 16 elderly patients, 7 were male (43.8%), and 9 were female (56.2%). The median age was 70.5 years (range, 60–80). The ORR was 93.8%, and 13 patients (81.3%) achieved a complete response (CR), 2 patients (12.5%) achieved a partial response (PR) and 1 patient had progressive disease (PD). It is noteworthy that all 5 patients who received chemotherapy-free regimens achieved CR. The median follow-up was 8.5 months (range, 2.7–22.9). The median PFS was not reached, and the 1-year PFS rate was 79.6%. A total of 81.3% of the patients maintained a response for at least 6 months, and 25% maintained a response for at least 12 months. All 3 patients aged ≥ 75 years achieved CR (100%). Haematologic AEs, including leukopenia (n = 15, 93.8%), neutropenia (n = 13, 81.3%), anaemia (n = 8, 50.0%) and thrombocytopenia (n = 4, 25.0%), were common. The most common nonhaematologic AEs were nausea and vomiting (n = 6, 37.5%), fatigue (n = 5, 31.3%) and decreased appetite (n = 5, 31.3%), most of which were limited in severity to grades 1 or 2 and improved with standard supportive care. Conclusions In the real world, selinexor-based regimens demonstrate good efficacy and controllable safety as first-line treatments for elderly patients with DLBCL.